Help, I am being held prisoner - Westlake, Donald E. (London : Titan Books, 2018)
Harry Künt, an incurable practical joker, has the opportunity to practice his craft in a new setting when he is sentenced to five-to-fifteen years in the state pen and roped into helping to plan an escape and two bank robberies.
Keywords: Prisoners -- Fiction; Practical jokes -- Fiction; Prisoners -- Fiction; Practical jokes -- Fiction; Mystery fiction; Humorous fiction; Mystery fiction